FIVE NEW MEXICAN MEMBRACIDAE - PLUMMER, CC (Laboratorio Paleontol, Petróleos Mexicanos, CD MEXICO, DF, MEX, 1944)
The genus, MEXAPHAENOPS (said to resemble Neaphaenops Jeannel), and M prietoi, are described The author sets up a series of 4 groups to indicate a possible evolutionary line spp living above ground in the tropics at elevations of 4000-6000 ft, with in
AN ESC NAC CIENC BIOL
Keywords: FIVE NEW, MEXICAN MEMBRACIDAE; CIENCIAS DE LA VIDA; BIOLOGIA VEGETAL; BOTANICA GENERAL